Transient Severe Respiratory Motion Artifacts After Application of Gadoxetate Disodium: What We Currently Know - Well, Lennart; Weinrich, Julius Matthias; Adam, Gerhard; Bannas, Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Background Gadoxetate disodium is an intracellular contrast agent for magnetic resonance imaging (MRI) of the liver. Recent publications revealed that injection of gadoxetate disodium can lead to imaging artifacts due to transient severe motion (TSM) in the arterial phase of contrast-enhanced liver MRI. In this review we present and discuss published frequencies of TSM, contrast injection and image acquisition protocols, potential risk factors, and proposed strategies to avoid or minimize the effects of TSM.Method Two reviewers independently searched the PubMed search engine for “transient severe motion artifact” and related terms. Reference lists of retrieved articles were also searched. The two reviewers selected in consensus nine studies that reported both frequencies of TSM and potential risk factors. Study data were extracted by both reviewers, and disagreement was resolved by consensus.Results and Conclusion TSM is caused by impaired breath-hold ability after gadoxetate disodium injection and occurs in 5 – 22 % of patients. The dose of applied contrast agent, repeated exposure to gadoxetate disodium, high BMI and pulmonary disease have been described as potential risk factors for TSM. However, there are only few concordant results on this topic and the pathophysiology of TSM has not been identified. Proposed strategies for the prevention of TSM are slow injection rates and low doses of diluted gadoxetate disodium. Accelerated and free-breathing MRI sequence protocols and breath-hold training may minimize the effects of TSM. Further prospective studies are needed to confirm these strategies and to identify the underlying mechanism of TSM.Key Points Citation Format
Keywords: transient severe motion artifacts; gadoxetate disodium; risk factors; dynamic contrast-enhanced MRI